Carbopeptoids: peptides and diketopiperazines incorporating the anomeric centre of mannopyranose - Long, D; Tennant-Eyles, R; Estevez, J; Wormald, M; Dwek, R; Smith, M; Fleet, G (2001)
An approach to the synthesis of D-mannopyranose derivatives incorporating an anomeric α-amino acid component is described. An N-acylated bicyclic [2.2.2] lactone, formed via an oxidative ring closure, provides access to a new class of glycopeptide analogues of D-mannopyranose and determines the anomeric configuration of compounds derived therefrom. The mannopyranose diketopiperazine may be equilibrated to the more stable furanose form under basic conditions; in general, mannopyranose derivatives containing an α-amino acid moiety at the anomeric position are less stable than the mannofuranose isomers.